Oat β-glucan and l-arabinose synergistically ameliorate glucose uptake in insulin-resistant HepG2 cells and exert anti-diabetic activity via activation of the PI3K/AKT pathway in db/db mice. Issue 19 (15th September 2022) - Wang, Sainan; Zhang, Tian; Li, Jiaxin; Zhang, Jiarui; Swallah, Mohammed Sharif; Gao, Junpeng; Piao, Chunhong; Lyu, Bo; Yu, Hansong
Abstract : The OBG : LA = 1 : 1 composition synergistically ameliorated glucose uptake in IR-HepG2 cells and exerted anti-diabetic activity via activation of the PI3K/AKT pathway in db/db mice. Abstract : Oat β-glucan (OBG) and l -arabinose (LA) have exhibited positive effects on diabetes and its complications. However, it is unclear whether OBG and LA have a synergistic effect. We investigated the effect of variable compositions (OBG : LA = 1 : 1, 1 : 2, 1 : 4, 1 : 6, 1 : 8, 1 : 10, 2 : 1, 4 : 1, 6 : 1, 8 : 1, 10 : 1) on glucose uptake in IR-HepG2 cells induced by dexamethasone (DEX) to find out the optimal composition showing synergistic effects. Furthermore, this study evaluated the anti-diabetic activity of the optimal composition in db/db mice. In vitro, the OBG : LA = 1 : 1 group showed the strongest synergistic effects among the varied compositions, outperforming OBG and LA alone. In vivo, there were more beneficial effects in the OBG : LA = 1 : 1 group compared with the OBG and LA single-dosing groups. OBG : LA = 1 : 1 supplementation markedly decreased the levels of fasting blood glucose (FBG) and insulin (INS) in serum, improved glucose tolerance and insulin sensitivity, lowered blood lipid levels, and reduced liver lipid accumulation. Moreover, the western blot results indicated that the OBG : LA = 1 : 1 group up-regulated the protein expression of glucose transporter-4 (GLUT4), phosphatidylinositol 3-kinase (PI3K), and phospho-protein kinase B (p-AKT), while down-regulating the protein expression of phospho-phosphorylated insulin receptor substrate-1 (p-IRS1) to enhance insulin transduction in liver tissues. These findings suggest that OBG : LA = 1 : 1 synergistically ameliorated glucose metabolism disorders and alleviated insulin resistance by promoting the PI3K/AKT pathway in the liver.